Clinical management of intrahepatic cholangiocarcinoma: surgical approaches and systemic therapies - Ruff, Samantha M.; Pawlik, Timothy M. (Frontiers in Oncology, 2024)
Intrahepatic cholangiocarcinoma (ICCA) is a rare and aggressive malignant tumor that arises from the biliary tracts in the liver. Upfront surgery with adjuvant capecitabine in patients with resectable disease is often the standard treatment. Unfortunately, only 20% of patients present with resectable disease and many individuals will develop recurrence or metastatic disease after curative-intent resection. Patients with advanced or metastatic ICCA often require multidisciplinary care with a combination of cytotoxic chemotherapy, targeted therapy, and/or locoregional therapies. Gemcitabine plus cisplatin is currently first line therapy for advanced or metastatic ICCA. In recent years, efforts have been focused to develop more effective targeted therapy, most commonly with FGFR and IDH inhibitors for ICCA. Despite these efforts, ICCA still carries a poor prognosis. We herein review the current clinical management of ICCA focusing on surgical technique and systemic therapies.